Circulating Lipopolysaccharides and Impaired Antioxidant Status in Patients With Atrial Fibrillation. Data From the ATHERO-AF Study - Menichelli, Danilo; Carnevale, Roberto; Nocella, Cristina; Cammisotto, Vittoria; Castellani, Valentina; Bartimoccia, Simona; Frati, Giacomo; Pignatelli, Pasquale; Pastori, Daniele (Frontiers in Cardiovascular Medicine, 2021)
Objectives. Atrial fibrillation (AF) is characterized by an oxidative imbalance, which is associated with an increased risk of cardiovascular events (CVEs). It is unclear whether low grade endotoxemia may contribute to the impaired antioxidant status in AF patients. We investigated the relationship between circulating lipopolysaccharides (LPS) and antioxidant status in AF patients. Patients and Methods. Post-hoc analysis from the ongoing prospective observational cohort ATHERO-AF study including 907 patients. Antioxidant status was evaluated by the activity of glutathione peroxidase 3 (GPx3) and superoxide dismutase (SOD). Patients were divided into two groups to evaluate the risk of CVEs: 1) LPS below median and GPx3 above median (n=254); 2) LPS above median and GPx3 below median (n=263). Results. The mean age was 73.5±8.3 years, and 43.1% were women. Median LPS and GPx3 were 50.0 pg/mL (interquartile range [IQR] 15-108) and 20.0 U/mL (IQR 10.0-34.0), respectively. Patients of Groups 2 were older, with a higher prevalence of heart failure. LPS above the median was associated with reduced GPx3 (Odds Ratio for LPS 1.752, 95% Confidence Interval [CI] 1.344-2.285, p<0.001) and SOD (OR 0.525, 95%CI 0.403-0.683) activity after adjustment for CHA2DS2VASc score. In a mean follow-up of 54.0±36.8 months, 118 CVEs occurred, . 42 in Group 1 and 76 in Group 2 (Log-Rank test p=0.001). At multivariable Cox regression analysis, Group 2 was associated with a higher risk of CVEs (Hazard Ratio [HR] 1.644, 95%CI 1.117-2,421, p=0.012), along with age ≥75 years (HR 2.035, 95%CI 1.394-2.972, p<0.001), diabetes (HR 1.927, 95%CI 1.280-2.900, p=0.002), and previous cerebrovascular disease (HR 1.895, 95%CI 1.251 Conclusions. Our study indicates that circulating LPS may contribute to impaired antioxidant status in patients with AF. Patients with coincidentally high LPS and reduced GPx3 activity showed the highest risk of CVEs.